Disciplining Gender? - Jackson, Cecile (World development, 2002)
Taken as a whole, research on gender issues in development, whether directly oriented to policy questions or to broader understandings of social change in developing countries, has been marked by a broad and deep disciplinary, multidisciplinary and interdisciplinary character which has been central to its success. Development agencies research strategies, however, particularly multilaterals, remain dominated by economics, which therefore constrains the extent to which other disciplines are able to contribute to development knowledge and policy evolution. The purpose of this paper is to argue that interdisciplinarity and multidisciplinarity must be sustained in researching gender and development, and that sociology, anthropology and politics are of increasing significance because of changing priorities in development. I argue that these disciplines have particular conceptual and methodological strengths, very briefly indicated, for researching gender and development, and that there is a need to resource these fields equally through capacity building in developing countries and renewed efforts to increase numbers of women researchers.